Measuring Leverage Effect of Covid 19 on Stock Price Volatility of Energy Companies Using High Frequency Data - Meher, Bharat Kumar; Hawaldar, Iqbal Thonse; Gil, Mathew Thomas; Dum, Deebom Zorle (International Journal of Energy Economics and Policy, 2021)
The uprising of the pandemic COVID-19 has paralysed the whole Indian economy, and as a result the Indian stock market is severely affected too. The widely inclusive lockdown articulated on 24th March 2020 by the Prime Minister as a careful step against COVID-19, trailed by ensuing augmentations, has brought about a halt of all financial movement in the country. The objective of the study is to frame different asymmetric price volatility models for Selected Companies under Energy Sector using 1-minute closing price from 15th October 2019 to 15th May 2020 to captivate the leverage effect of the pandemic. The asymmetric terms in the selected asymmetric models are providing sufficient proof that the stock price volatility of three companies out of six under NIFTY Energy i.e., BPCL, Power grid and Indian Oil Corporation are unfavourably influenced by the pandemic. The forecasting graphs for volatility of four companies have been plotted, reveals that there is consistency in the stock price returns of all these four companies but the graph of predicted variance of Indian Oil Corporation reveals that the volatility has been fluctuating drastically with many high peak variances or fluctuations during the two days of forecasted period. Keywords: Asymmetric Volatility, EGARCH, GJR-GARCH, TGARCH, High frequency Data JEL Classifications: C40, C530, C550, C580, G110, G120, G170 DOI: https://doi.org/10.32479/ijeep.11866